Synthesis and Evaluation of a Non-Peptide Small-Molecule Drug Conjugate Targeting Integrin αVβ3 - Paulus, Jannik; Sewald, Norbert (Frontiers in Chemistry, 2022)
An integrin αVβ3-targeting linear RGD mimetic containing small molecule-drug conjugate (SMDC) was synthesised by combining the antimitotic agent MMAE, an enzymatically cleavable Val-Ala-PABC linker with a linear conjugable RGD mimetic. The structure proposal for the conjugable RGD mimetic was suggested upon DAD mapping analysis of a previously synthesised small-molecule RGD mimetic array based on a tyrosine scaffold. Therefore, a diversifying strategy was developed as well as a novel method for the partial hydrogenation of pyrimidines in presence of the hydrogenolytically cleavable Cbz group. The small-molecule RGD mimetics were evaluated in an ELISA-like assay and the structural relationships were analysed by DAD mapping revealing activity differences induced by structural changes as visualised in dependence on special structural motifs. This provided a lead structure for generation of an SMDC containing the antimitotic drug monomethylauristatin E (MMAE). The resulting SMDC containing a linear RGD mimetic was tested in a cell adhesion and an in vitro cell viability assay in comparison to reference SMDCs containing cRGDfK or cRADfK as homing device. The linear RGD SMDC and the cRGDfK SMDC inhibited adhesion of the αVβ3-positive WM115 cells to vitronectin with IC50 values in the low µM range, while no effect was observed for the αVβ3-negative M21-L cell line. The cRADfK SMDC used as negative control was about 30-fold less active in the cell adhesion assay than the cRGDfK SMDC. Conversely, both the linear RGD SMDC and the cRGDfK SMDC are about 55-fold less cytotoxic than MMAE against the αVβ3-positive WM115 cell line with IC50 values in the nM range, while the cRADfK SMDC is 150-fold less cytotoxic than MMAE. Hence, integrin binding also influences the antiproliferative activity giving a targeting index of 2.8.